MULTIMEDIA PEMBELAJARAN PENGENALAN KATEGORISASI HEWAN - Zohri, M Fahrozan; Jangcik, Idi; Yuhelmi, Yuhelmi (Universitas Lancang Kuning, 2023)
This study aims to design a multimedia learning introduction to the categorization of animals classified as herbivores, carnivores, and omnivores. The background of this research is that it is very easy for children to understand explanations in the cartoons or animations they watch. The impact if the lack of desire of children to learn can be bad for the children themselves and also this nation. This learning multimedia is designed using the ADDIE model system development method with five process stages, Analysis, Design, Development, Implementation and Evaluation. The data collection method used in this study was observation, interview, documentation and library study. The application used for the development of this learning media was Adobe Flash. The research instrument consisted of a validity questionnaire. Product verification is carried out by two validators who are competent in the aspects of material and design. The results of the product validation developed in terms of material aspects fulfill the validity of 98%, achieving very valid criteria. Furthermore, the design aspect with valid criteria has a validity percentage of 87%. Based on the testing stages, it can be concluded that learning multimedia applications are identified as valid for use as teaching materials.